Association between Smoking and Colposcopic and Cytological Findings in Cervix Uteri - سلمان صفاء; عيسى رنا; علي مهاد (Latakia University Journal -Medical Sciences Series, 2020)
The aim of this study was to identify the relationship between smoking and the presence of colposcopic and cytological abnormalities in cervix uteri. Methods: an observational study was initiated to investigate this relationship in the department of Obstetrics and Gynecology at Tishreen University Hospital from October 2018 to December 2019. All patients submitted to colposcopy and Papanicolaou smear. The chi-square test for categorical variables was used to determine the significance of association. Results: A total of 100 patients met the inclusion criteria, were divided into smokers group (70) patients and non-smokers group (30) patients. We found that there was important difference in the rate of abnormal colposcopic findings between two groups. This rate in smoker sample was: 45.7% and in the second was 26.7% with p-value=0.04. Additionally, there was difference in the rate of abnormal cellular findings. This rate in first group was 32.9% whereas in the second was 23.4% with p-value=0.6. Conclusion: Our data suggest that smoking increase abnormalities that detect in Papanicolaou smear and colposcopy.